Control of grasshoppers, particularly Hieroglyphus daganensis, in northern Benin using Metarhizium flavoviride - Lomer, C.J.; Thomas, M.B.; Douro-Kpindou, O.K.; Gbongboui, C.; Godonou, I.; Langewald, J.; Shah, P.A. (Cambridge University Press, 1997)
Trials on the use of Metarhizium flavoviride Gams and Roszypal conidia in oil-based formulation for the control of grasshoppers, particularly Hieroglyphus daganensis Krauss, in Malanville, north Benin, are described. Preliminary work examined sprayer types, application rate, and time of application. In a trial on 4-ha plots with three replicates, M. flavoviride mycoinsecticide application to H. daganensis nymphs resulted in field population reductions of 70% after 14 days. In samples incubated in cages, mortality was higher in the samples taken 3 or 7 days after application than in the sample taken immediately after application, indicating the possibility of residual pick-up compared with direct spray impact in this environment. Significant mortality was still being observed in samples collected 37 days after application; to investigate this further, a method for bioassaying the spore load in the field was developed and used to monitor the spore load in the field. The possibility that the results indicate the occurrence of secondary infections resulting from horizontal transmission of M. flavoviride is discussed